RESPONSE OF SUB1 INTROGRESSION LINES OF RICE TO VARIOUS FLOODING CONDITIONS - Yudhistira Nugraha; Georgiana V. Vergara; David J. Mackill; Abdel Bagi Ismail (Indonesian Journal of Agricultural Science, 2013)
Two types of floods can be happen in rice crops, i.e. flash floods and  stagnant floods. Flash floods cause complete submergence for up to 2 weeks, while stagnant floods (SF) could partially submerge part of rice  plant. To overcome yield loss due to the floods, introgression of SUB1 gene, known as a gene suppressing cell elongation and carbohydrate  metabolism, to rice genotype can increase plant tolerance to complete submergence for 10 days or more. The study aimed to evaluate the response of 18 rice genotypes, including the recently developed sixth pair SUB1 near isogenic lines (NILs) of mega-rice varieties (Swarna, Sambha Mahsuri, IR64, TDK1, BR11, and CR1009), to various flooding conditions. The rice genotypes were planted at field ponds at Los Banos, Philippines, in the wet season (WS) of 2009. The treatments were 15 days  submergence, SF, SF follows submergence and normal conditions. Each treatment was arranged in completely randomized block design with threereplications. The results showed that the SUB1 introgression rice lines had higher survival compared to the non-SUB1 and did not much elongate their shoots during submergence. Nevertheless, under SF the rice genotypes should elongates their shoots to allow restoring contact with the air. SF and SF follows submergence decreased the panicle number, grainnumber per panicle and panicle fertility. Consequently, the yield declined. It suggests that sensitive genotypes are mostly sourcelimited during grain filling. The SUB1 introgression lines had higher chlorophyll concentration and less depletion in soluble sugar and starch after submergence. Under SF, soluble sugar and starch contents between the SUB1 NILs and  non-SUB1 lines were not significantly different. Introgression of the SUB1 into high-yielding varieties improved submergence tolerance without affecting yield potential. The study indicates that introgression of the SUB1 into taller type rice varieties should be done to compensate the effect of suppressed elongation.